Trends in home smoking bans in the USA, 1995–2007: prevalence, discrepancies and disparities. Issue 3 (3rd August 2011) - Zhang, Xiao; Martinez-Donate, Ana P; Kuo, Daphne; Jones, Nathan R; Palmersheim, Karen A
Abstract : Background: Home smoking bans significantly reduce the likelihood of secondhand smoke exposure among children and non-smoking adults. The purpose of this study was to examine national trends in (1) the adoption of home smoking bans, (2) discrepancies in parental smoking ban reports and (3) household and parental correlates of home smoking bans among households with underage children from 1995 to 2007. Methods: The authors used data from the 1995–1996, 1998–1999, 2001–2002, 2003 and 2006–2007 Tobacco Use Supplement of the US Current Population Survey to estimate prevalence rates and logistic regression models of parental smoking ban reports by survey period. Results: Overall, the prevalence of a complete home smoking bans increased from 58.1% to 83.8% (p<0.01), while discrepancies in parental reports decreased from 12.5% to 4.6% (p<0.01) from 1995 to 2007. Households with single parent, low income, one or two current smokers, parents with less than a college education or without infants were consistently less likely to report a home smoking ban over this period (p<0.05). Conclusions: Despite general improvements in the adoption of home smoking bans and a reduction on parental discrepancies, disparities in the level of protection from secondhand smoke have persisted over time. Children living in households with single parents, low income, current smoker parents, less educated parents or without infants are less likely to be protected by a home smoking ban. These groups are in need of interventions promoting the adoption of home smoking bans to reduce disparities in tobacco-related diseases.